(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction.The purpose of the present paper was to study the effect of sodium hyaluronate on the pathochemical process in the anterior eye segment when using benzalkonium chloride eye drops in glaucoma patients Material and Methods. The patients were divided into two groups: Control group consisted of 25 glaucoma patients being instilled Latanoprost with benzalkonium chloride (BAC); Study group consisted of 36 patients being additionally instilled 0.1% sodium hyaluronate solution for 6 months. In the tear fluid we determine the activity of lactate dehydrogenase (LD), glucose-6-phosphate dehydrogenase (G-6-PD), malate dehydrogenase (MDH), and acid phosphatase (ACP), as well as levels of thiol and disulfide groups [8]. Results. Data obtained in the studying of enzyme activity in the tear fluid of patients receiving hyaluronate instillations in addition to BAC eye drops indicate clearly the membrane-stabilizing action of hyaluronate. Meanwhile, hyaluronate did not influence significantly on reduced glutathione level in the tear, decreasing markedly the content of oxidized coenzyme. Conclusions. Using hyaluronate in patients receiving BAC-containing antiglaucoma drugs has been shown to prevent destabilization of anterior segment membrane structure tissues. This is evidenced by a clear decrease in activity level of corresponding enzyme markers in the tear fluid. When using hyaluronate in patients receiving BAC-containing drops, thiol level in the tear fluid does not change significantly; this is the evidence of direct membrane trophic protective activity of hyaluronate from detergent action of the preservative.